The age and genomic integrity of neurons after cortical stroke in humans - Huttner, Hagen B; Bergmann, Olaf; Salehpour, Mehran; Rácz, Attila; Tatarishvili, Jemal; Lindgren, Emma; Csonka, Tamás; Csiba, László; Hortobágyi, Tibor; Méhes, Gábor; Englund, Elisabet; Solnestam, Beata Werne; et al. (Nature neuroscience, 2014)
In this study, the authors use measures of carbon-14 in neuronal DNA from human stroke patient cortical tissue samples to show that, unlike previous studies done in rodents, they do not find any evidence of increased neurogenesis after an ischemic injury. In addition, DNA damage assays suggest that there is no increase in DNA rearrangement after this insult. It has been unclear whether ischemic stroke induces neurogenesis or neuronal DNA rearrangements in the human neocortex. Using immunohistochemistry; transcriptome, genome and ploidy analyses; and determination of nuclear bomb test–derived 14 C concentration in neuronal DNA, we found neither to be the case. A large proportion of cortical neurons displayed DNA fragmentation and DNA repair a short time after stroke, whereas neurons at chronic stages after stroke showed DNA integrity, demonstrating the relevance of an intact genome for survival.